The Correlation between Local Culinary Eating Patterns With Symptoms of GERD in Bank Employees in Soe City, East Nusa Tenggara - Cynthia Candra Dinawati Liu; Regina M. Hutasoit; Rahel Rara Woda; Efrisca M. Br. Damanik (Universitas Nusa Cendana, 2025)
Background: The prevalence of GERD has increased in all age groups with the highest incidence in the age group of 20 to 45 years. Bank employees are in the reproductive age group who have time demands of work, which require longer working hours with lifestyle changes and are at risk of developing GERD. Changes in eating patterns with spicy, sour and fatty foods such as corn bose, sei meat, sambal luat and tangerine soe if consumed frequently and in excessive amounts can cause heartburn and regurgitation complaints.Methods: This study uses an analytical observational research design with a cross sectional design conducted on bank employees in Soe City, East Nusa Tenggara using a local culinary diet questionnaire and a gastroesophageal reflux disease questionnaire (GERD-Q). Sampling using total sampling technique and obtained 99 research subjects who meet the inclusion criteria.Results: From the results of the contingency coefficient test, there is no relationship between local culinary eating patterns with GERD symptoms in bank employees in Soe City, East Nusa Tenggara.Conclusion: there is no correlation between local culinary eating patterns with GERD symptoms in bank employees in Soe City, East Nusa Tenggara.